Influence of Baseline Macular Edema on Cost Evaluation of Panretinal Photocoagulation vs Intravitreal Ranibizumab for Proliferative Diabetic Retinopathy. (September 2019) - Lin, James; Yannuzzi, Nicolas A.; Chang, Jonathan S.; Sridhar, Jayanth; Smiddy, William E.
Purpose: This article evaluates the influence of baseline diabetic macular edema (DME) on cost-utility analysis of treatment for proliferative diabetic retinopathy (PDR) based on 5-year Diabetic Retinopathy Clinical Research Network (DRCR.net ) Protocol S results. Methods: A decision-analysis model calculated comparative cost utility of panretinal photocoagulation (PRP) and intravitreal ranibizumab (IVR) treatment for PDR with and without baseline DME. Centers for Medicare & Medicaid Services data were used to calculate associated modeled costs in a hospital/facility-based and nonfacility setting. Cost utility was calculated based on the preserved visual utility and estimated life years remaining. Sensitivity analyses were performed to evaluate the impact of the model's assumptions. Results: The modeled cost per quality-adjusted life year (QALY) of treatment for PDR with baseline DME for 5 years of utility in the facility (nonfacility) setting was 280, 919 (203, 444) in the PRP group and 452, 387 (339, 319) in the IVR group. The estimated lifetime cost per QALY in the facility (nonfacility) setting was calculated as 84, 761 (50, 077) in the PRP group and 314, 483 (230, 301) in the IVR group. The cost per QALY of IVR for the first 5 years of treatment was 1.6 to 1.7 times that of PRP, whereas lifetime cost per QALY was 3.7 to 4.6 times higher. When considering all patients regardless of baseline DME status, lifetime cost per QALY of PRP was 8% to 13% higher, whereas IVR was only 1% higher compared with the cost per QALY without baseline DME. Conclusions: When considering the subset of patients with PDR and baseline DME, PRP maintains a more favorable cost utility compared with IVR. This augments previous reports that PRP has a more favorable cost utility than IVR for PDR without DME, given the marginal visual benefit of IVR.